Hubungan Kadar Asam Urat dengan Kadar Kolesterol HDL pada Peserta Prolanis di Puskesmas Kedaton Bandar Lampung - Andi Eka Yunianto; Sutrio (Journal of Dietetics Science, 2025)
Uric acid and High-Density Lipoprotein (HDL) are important biomarkers associated with the risk of metabolic and cardiovascular diseases. Hyperuricemia is known to increase the risk of hypertension, metabolic syndrome, and heart disease, while low HDL levels contribute to atherosclerosis. However, the relationship between uric acid and HDL levels is still not entirely consistent in various studies. This study aims to analyze the relationship between uric acid and HDL levels in Prolanis patients at the Kedaton Community Health Center, Bandar Lampung. The study used a cross-sectional design involving 42 respondents aged 42–76 years. Data were collected through venous blood examination of 8 ml. HDL levels were measured using the Chod-Pap method, while uric acid levels were measured using the Uricase method. Data analysis used the Pearson test with a significance level of p <0.05. Based on the average HDL level of respondents was 49.79 ± 7.67 mg/dl, while uric acid levels were 7.17 ± 8.13 mg/dl. Correlation analysis showed a significant positive relationship between uric acid levels and HDL (r=0.339; p=0.028). There was a positive relationship between uric acid levels and HDL, indicating that uric acid, at certain levels, may act as an antioxidant that supports lipid metabolism. However, high uric acid levels remain a risk factor for metabolic disease. Further research with larger samples is needed to confirm these findings.